Study on Gear Whine of Hybrid Power System based on Contact Patch and Micro Modification - Zhuokai Peng; Jing Liu; Fei Xiong; Dan Wei (Jixie chuandong)
Gear whine noise of one hybrid power system is analyzed and optimized. Based on test noise order analysis， the main noise source is found. The contact patch test also shows that eccentric load phenomenon is obvious. The simulation and test results of contact patch are compared. It shows that the simulation results are coincident with test results， this simulation model could be used for the following micro parameter optimization analysis. The micro parameters of the first pinion gear are optimized. The contact patch of the optimized gear is more uniform， and transmission error is smaller， and the bearing dynamic responses are smaller. Noise test result shows that noise of gear micro modified became lower.